Pengaruh Konsumsi Energi Terbarukan dan Tidak Terbarukan terhadap Emisi Karbon di Indonesia - Gabriella Losa Pongtuluran; Ni Putu Wiwin Setyari (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to empirically analyze the effects of renewable energy consumption, non-renewable energy consumption, Gross Domestic Product (GDP), and population size on carbon emission levels in Indonesia during the observation period from 1990 to 2023. The study employs a quantitative approach using the Error Correction Model (ECM) to identify both short-run and long-run relationships among the variables examined. Prior to model estimation, stationarity tests and cointegration tests using the Engle–Granger and Johansen approaches were conducted to ensure the existence of a long-run equilibrium relationship. The estimation results indicate that in the short run, renewable energy consumption, non-renewable energy consumption, and GDP do not have a significant effect on carbon emissions. In contrast, population size is found to have a positive and significant impact on the increase in carbon emissions. The Error Correction Term (ECT–1) is statistically significant and negative, indicating the presence of a strong adjustment mechanism toward long-run equilibrium. In the long run, all variables are proven to be cointegrated. Non-renewable energy consumption and population growth contribute to higher carbon emissions, while renewable energy consumption plays a role in reducing emissions. GDP also tends to increase carbon emissions unless economic growth is directed toward green and sustainable development.